An Applied Study to Evaluate the Achievement of School Buildings by Using (CPM)and(Fuzzy CPM) Methods - Abbas , Duaa; Al-Rashidi , Hanan (The Gulf Economist, 2024)
Abstract The absence of scientific planning methods in the management of construction project,if neglected,will lead to unsatisfactory performance for all parformance for all parties charged with the completion of the project. This is evident in the lack of comprehensive knowledge of the process of planning,follow-up, and scheduling for the construction of the project from the theoretical and practical aspects, especially when there is vague and unclear data and information or there is a lack of information related to the time period or costs required to implement the project.Therefore,project management must seek to improve that knowledge through the introduction of effective and exceptional scientific methods to ensure a successful and integrated project within the required specifications and in a record period and lower cost. For this reason,it is necessary to find a more practical way to solve this problem through the use of the Critical Path method and Fuzzy Logic theory in order to calculate the optimal time of completion, and this is done through the program(Win QSB)